Study guides

Q: Solve by substitution method y equals -4x - 7 y equals 3x?

Write your answer...

Submit

Related questions

If you mean: 3x-3y = 9 and y-3x = -3 then by adding both equations y = -3 and by substitution x = 0

-3x = 3 + y 3 + y - 5y = -21 -4y = -24 y = 6 x = -3

If: x+y = 4 and y = 2x+1 Then: 4-x = 2x+1 => 3 = 3x => 1 = x So by substitution: x = 1 and y = 3

From first equation, -y = 3x + 3. Substitute in second equation: -3x + 5(3x + 3) = -21 ie 12x = -36 so x = -3 and y = -(-9 + 3) = 6. Easier method: subtract first equation from second giving -4y = -24 so y = 6, this in first equation gives -6 = 3x + 3, ie 3x = -9 so x = -3

(2,-2)

solve -3x-3y=-15

what does the equation equal? if it equals zero: 0= 3x(4-11) 0=3x(-7) 0=3x 0=x if the equation doesn't equal anything, it means it's just an expression meaning you can't solve for x, you can only reduce (and this equation is already reduced). if the equation equals y, you need another equation and use either substitution or elimination to solve for x.

4x-y=2, thereforey=4x-2sub y into 3x+2y=6...3x+8x-4=611x=10x=10/11

You solve one of the equation for one of the variables. For example, if the variables involved are "x" and "y", you might solve for "y". It doesn't really matter what variable you solve for first, so you can solve for whatever variable is easiest to solve. Then - assuming you got, for example, "y = 3x -1", in this example you would replace every "y" by "3x - 1" in the other equation or equations.

y=16 x= -4

If you mean: x+7y = 39 and 3x-2y = 2 Then by substitution: x = 4 and y = 5

If: x+y = 8 and 2x-y = 5 Then by adding the equations together: 3x = 13 or x = 13/3 By substitution into the original equations: x = 13/3 and y = 11/3

3x+5=20 3x=15 x=5

3x + 2y = 12 ie 2y = 12 - 3x so y = 6 - 3x/2

If you mean x+2y = -2 and 3x+4y = 6 then by solving the simultaneous equations by substitution x = 10 and y = -6

2y-3x=4

3x-11 for x=9

2x-y=3 2/3x-y=-1

x+2(x+3) = 12 x+2x+6 = 12 x+2x = 12-6 3x = 6 x = 2 and y = 5

Substitution method: y = 1 + x so 2x + (1 + x) = 4, ie 3x = 3 so x = 1 and y = 2

For substitution, you would substitute y=3x-4 into 6x + y = 2 ---> 6x + (3x-4) = 2. 6x + 3x - 4 = 2 ---> 9x - 4 =2 ---> 9x = 6 ---> x = 6/9 = 2/3. Then substitute x = 2/3 into one of the original: y = 3(2/3) - 4 = 2-4 = -2. So you have (2/3,-2). Check in the other equation: 6(2/3) + -2 = 2 ---> 4 + -2 = 2 [this checks]

It is not possible to do so because the question contains one equation (5x + y = 1) and one expression (3x + 2y + 2). An expression cannot be solved.

3x=24 x=8

By elimination: x = 3 and y = 0

3x + 2y = 4; 2x - 2y = 16 Add; 5x = 20 so x = 4 and y is therefore -4